The Tendency Of Same-Sexual Orientation In Adolescents Judging From The Intention To Access LGBT Content On Social Media (PT. LARPA JAYA PUBLISHER, 2023)
Adolescence is a critical period in which individuals begin to explore and identify their sexual orientation as part of their developing sexual identity. Teenagers often seek to express themselves and demonstrate their presence in the world, frequently through social media platforms. However, excessive or unmoderated use of social media can lead to miscommunication or exposure to inappropriate content, including content related to LGBT issues. This study aims to examine the influence of adolescents’ intention to access LGBT content on social media on the development of same-sex sexual orientation tendencies. A quantitative approach was employed, focusing on two variables: intention to access LGBT content and same-sex sexual orientation. Data were collected from 181 respondents aged 15–22 years using a Likert-scale questionnaire to measure both sexual orientation and intentions. The results reveal a significant positive relationship between same-sex sexual orientation and the intention to access LGBT content, with a correlation coefficient of 0.903 and an effective contribution of 81.6%. The significance test yielded a p-value of 0.000, which is less than 0.05, indicating that the relationship is statistically significant. These findings suggest that adolescents’ engagement with LGBT content on social media is strongly associated with tendencies toward same-sex sexual orientation, highlighting the influential role of social media in sexual identity development during adolescence.